One-Year Outcomes of Aflibercept in Treat-and-Extend Versus Pro Re Nata Regimens for Bevacizumab-Resistant Diabetic Macular Edema: A Real-World Study - Yozgat, Zubeyir; Isik, Mehmed Ugur; Sabaner, Mehmet Cem (Springer Science and Business Media LLC, 2024)
The aim of this study was to compare the efficacy of the treat-and-extend (TAE) regimen versus the pro re nata (PRN) regimen in patients with bevacizumab-resistant diabetic macular edema (DME) treated with aflibercept, with or without adjunctive laser therapy.Ninety-one eyes from 91 patients who were switched to aflibercept after three consecutive intravitreal bevacizumab injections for the treatment of DME were included in this retrospective real-world study. The patients were categorized into three groups: TAE (n = 30), TAE + laser (n = 31), and PRN (n = 30). Changes in best-corrected visual acuity and central macular subfield thickness (CMST) at 12, 24, and 52 weeks were defined as the primary functional and anatomical outcomes.A total of 91 eyes from 91 patients (49.5% female) with a mean age of 63.9 ± 7.1 years were included in the analysis. At 52 weeks, the mean letter gains were 8.03, 8.90, and 10.23 in the TAE, TAE + laser, and PRN groups, respectively. Anatomical improvements, as measured by CMST reduction, were 55.33 µm, 33.35 µm, and 48.96 µm in the TAE, TAE + laser, and PRN groups, respectively. The average number of injections administered was 7.7, 8.1, and 8.1, respectively. The final extension interval for the TAE group was 8.7 weeks, compared to 9.5 weeks in the TAE + laser group.The PRN group demonstrated the highest functional improvement while the TAE group showed the greatest anatomical improvement. Overall, both anatomical and functional outcomes in the TAE regimen were comparable to the PRN regimen in patients with bevacizumab-resistant diabetic macular edema.
Keywords: Pro re nata regimen; Ophthalmology; Bevacizumab-resistant; Treat-and-extend regimen; Diabetic macular edema; Real-world study; RE1-994; Aflibercept; Original Research